A preliminary study on the diversity of invertebrates associated with Corallina officinalis Linnaeus in southern Istrian peninsula - Buršić, Moira (Array, 2019)
Red coralligenous algae Corallina officinalis provides shelter to many invertebrate species from wave actions, predation and desiccation stress in the intertidal area. Physical structure and complexity of the habitat have a major influence on biodiversity of this community. The aim of this preliminary study was to examine the diversity of invertebrate assemblages inside the red algae C. officinalis turf. Three sampling locations were chosen where algal cover range was above 90%. On each location sampling was done quantitatively by scraping off within 3 replicate quadrats 20 x 20 cm in size. A total of 30,518 specimens were isolated from all sampling locations. The prevalent groups were amphipod crustaceans, polychaetes, bivalves and gastropods that made a total of 86% of all macrofaunal groups associated with algal turfs. The most abundant group were amphipods that made 42% of the total separated individual invertebrates. Our study demonstrated that C. officinalis is a very important habitat with high abundance and diversity of invertebrate assemblages.